A stepwise approach to move from a cleavage-stage to a blastocyst-stage transfer policy for all patients in the IVF clinic. Issue 3 (22nd September 2020) - De Croo, I; De Sutter, P; Tilleman, K
Abstract: STUDY QUESTION: Is a stepwise change management approach an efficacious method to move from a Day 3 transfer policy to a Day 5 transfer policy for all patients in an IVF program? SUMMARY ANSWER: A stepwise change from a Day 3 to a Day 5 transfer policy maintained the live birth rates per oocyte collection cycle (OCC) of the IVF program, with increased single embryo transfer (SET) and reduction of twin pregnancies. WHAT IS KNOWN ALREADY: Evidence has shown that the probability of a live birth following IVF with a fresh embryo transfer (ET) is significantly higher after blastocyst-stage transfer than after cleavage-stage transfer. Blastocyst culture and transfer are usually performed in cases of good prognosis patients but many centers keep transferring cleavage-stage embryos for most of their patients because of the higher transfer cancelation rate in a blastocyst transfer policy. STUDY DESIGN, SIZE, DURATION: In January 2012, a Day 5 embryo culture and blastocyst transfer policy including vitrification of supernumerary Day 5 blastocysts were implemented in a stepwise approach. The retrospective descriptive single-center analysis involving a preintervention phase consisted of Day 3 ETs and Day 3 slow freezing from 2010 until 2012. The postintervention phase involved a 6-year period from 2012 until 2017 in which three consecutive changes in the transfer policy were made, each over a 2-year period, based on the number of zygotes on Day 1. The primary outcome was live birth delivery rate per OCC during the stepwise change. PARTICIPANTS/MATERIALS, SETTING, METHODS: All patients with at least one zygote available on Day 1 were scheduled for a fresh transfer, either on Day 3 or 5. Cycles with preimplantation genetic testing, freeze-all and oocyte donation cycles and cycles with a Day 2 transfer in the preintervention period were excluded. In the preintervention group, all cycles were scheduled for Day 3 transfer (n = 671 OCC) and slow freezing of the remaining Day 3 embryos. In the postintervention period, three periods were analyzed: period 1 (n = 1510 OCC; 1–9 zygotes: Day 3 transfer and >9 zygotes: Day 5 transfer); period 2 (n = 1456 OCC; 1–4 zygotes: Day 3 transfer and >4 zygotes: Day 5 transfer) and period 3 (n = 1764 OCC; Day 5 transfer). All remaining embryos underwent extend culture and were vitrified on Day 5, if developed to at least an early blastocyst. Data were analyzed using a mixed regression model with patient as a random factor. MAIN RESULTS AND THE ROLE OF CHANCE: In the preintervention group, all OCC were scheduled for a Day 3 transfer. In period 1, period 2 and period 3, 20.9%, 61.5% and 100% of the OCCs were scheduled for a Day 5 transfer, respectively. More transfers per OCC were canceled in the postintervention period 2 and period 3 compared to the preintervention period (5.3% and 18.7% versus 3.4%, respectively; P  < 0.0001). The mean number of embryos used per transfer decreased gradually after the introduction of the Day 5 transfer policy, from 1.62 ± 0.65 in the preintervention group to 1.12 ± 0.61 in period 3 ( P  < 0.0001). The percentage of SET cycles increased from 48.4% in the preintervention group to 54.6%, 73.8% and 87.8% in period 1, period 2 and period 3, respectively ( P  < 0.0001). The mean number of cryopreserved surplus embryos was significantly lower in period 3 compared to the preintervention group (1.29 ± 1.97 versus 1.78 ± 2.80; P  < 0.0001). Pregnancy and live birth delivery rate per fresh transfer, respectively, were significantly lower in the preintervention group (26.7% and 19.1%) as compared to period 3 (39.3% and 24.2%) ( P  < 0.0001). Twin pregnancy rate decreased gradually from 11.0% to 8.2%, 5.7% and 2.5% in the preintervention group, period 1, period 2 and period 3, respectively ( P  < 0.0001). Live birth rate and cumulative live birth delivery rates per OCC were significantly higher in group 2 compared to the preintervention period (25.6% and 35.8% versus 18.5% and 25.9%, respectively). Similar live birth and cumulative live birth delivery rates per OCC were achieved between the preintervention period and period 3 (18.5% and 25.6% versus 19.7% and 24.9%; respectively). LIMITATIONS, REASONS FOR CAUTION: The primary limitation is the retrospective design of the study. The allocation of the cycles was done by the number of zygotes available without taking into account both embryological and clinical prognostic factors. Furthermore, the analysis was restricted to cycles where the standard transfer policy was followed. Embryos which were in the morula or compaction stage were not vitrified or cultured to Day 6, which could have contributed to the slight, not statistically significant, drop in live birth rate per OCC in group 3. WIDER IMPLICATIONS OF THE FINDINGS: Live birth and cumulative live birth delivery rate per OCC in an unselected patient population is maintained in a Day 5 transfer policy compared to a Day 3 transfer policy. Additionally, a significantly reduction in twin pregnancy rate and a significant increase in SET were observed in a Day 5 transfer policy. For centers wanting to make the step from Day 3 to Day 5, this study provides a practical stepwise change management approach. STUDY FUNDING/COMPETING INTEREST(S): None. TRIAL REGISTRATION NUMBER: None.